2017
DOI: 10.1016/j.mad.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Enforced DNA repair enzymes rescue neurons from apoptosis induced by target deprivation and axotomy in mouse models of neurodegeneration

Abstract: It is unknown whether DNA damage accumulation is an upstream instigator or secondary effect of the cell death process in different populations of adult postmitotic neurons in the central nervous system. In two different mouse models of injury-induced neurodegeneration characterized by relatively synchronous accumulation of mitochondria, oxidative stress, and DNA damage prior to neuronal apoptosis, we enforced the expression of human 8-oxoguanine DNA glycosylase (hOGG1) and human apurinic-pyrimidinic endonuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 99 publications
0
18
0
Order By: Relevance
“…The apoptotic disassembly of motor neurons could begin regionally near dysfunctional mitochondria and spread to a wider area, resulting in motor neuronal death. Our speculation is supported from data that show that in aging-associated neural diseases, there is a loss of mitochondrial function leading to increased mPTP sensitivity, and attenuated mitophagy that contributes to apoptosis (32, 68, 86, 99, 111). Nevertheless, we do not have data to support a process of aging associated localized motor neuron disassembly outside of neural degenerative disease.…”
Section: Local Apoptotic Signaling In Aging Muscles and Motor Neuronsmentioning
confidence: 55%
See 2 more Smart Citations
“…The apoptotic disassembly of motor neurons could begin regionally near dysfunctional mitochondria and spread to a wider area, resulting in motor neuronal death. Our speculation is supported from data that show that in aging-associated neural diseases, there is a loss of mitochondrial function leading to increased mPTP sensitivity, and attenuated mitophagy that contributes to apoptosis (32, 68, 86, 99, 111). Nevertheless, we do not have data to support a process of aging associated localized motor neuron disassembly outside of neural degenerative disease.…”
Section: Local Apoptotic Signaling In Aging Muscles and Motor Neuronsmentioning
confidence: 55%
“…In neurons, DNA damage precedes neuronal apoptosis (85), whereas forced repair of DNA damage rescues neurons from elimination by apoptosis (86). Indeed, increased mtDNA mutations have been found in fiber regions that contain oxidative damage (2, 90).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to SMA motor neurons (this study), accumulation of phospho-p53 S15 has been documented in human stem cell-derived motor neurons from C9ORF72-related ALS patients (Lopez-Gonzalez et al, 2016) and that of phospho-p53 S18 in neonatal axotomized mouse motor neurons (Martin and Wong, 2017). However, the functional relevance of this specific modification for the neurodegenerative process was not previously investigated in any disease models.…”
Section: Discussionmentioning
confidence: 66%
“…In a recent study, a neuroprotective role of BER machinery was demonstrated in mouse model. Martin et al enforced expression of human APE1 and OGG1 in vulnerable neurons and found that the expression significantly suppressed the axotomy and target deprivation induced apoptosis of thalamic neurons and motor neurons, which indicates that the modulation of DNA repair could be a potential therapeutic target for DNA damage related neuronal apoptosis [244]. Another study revealed that, overexpression of sirtuin 6 (SIRT6), which is down-regulated in brains of AD patients as well as 5XFAD mice, likely regulated by Aβ42, prevents Aβ42-induced DNA damage in a p53-depedent manner [244, 245].…”
Section: Discussionmentioning
confidence: 99%